Species of Neoperla (Plecoptera: Perlidae) from Henan Province, China - Li, Weihai; Li, Shan; Feng, Guangwei; Wang, Yunbing (Zootaxa, 2014)
A new species, Neoperla jigongshana Li & Li, sp. nov., is proposed from Henan Province, China and compared with related congeners. Two additional species, N. cavaleriei (Navás, 1922) and N. forcipata Yang & Yang, 1992, are reported from the Province for the first time and descriptions of female and egg of N. baotianmana Li & Wang, 2011 are also presented. A provisional key to the known species of the Henan Province is presented.